EXPERIENTIAL MARKETING, EMOTIONAL BRANDING, AND BRAND TRUST AND THEIR EFFECT ON LOYALTY ON HONDA MOTORCYCLE PRODUCT - Nuruni Ika Kustini (Journal of Economics, Business, and Accountancy Ventura, 2011)
The rising globalization era has demanded that the world should change from the old para- digms into the new one in every aspect, especially in marketing world. Nowadays, to win over the market share cannot not only do a business that relies on the functionality of their prod- ucts, but also take into account its brand attributed to their products as it delivers certain images in the mind of consumers or end-users. This research aimed to acknowledge the im- pacts of experiential marketing, emotional branding and brand trust towards loyalty on Honda motorcycle products.  Variables  in  this  research  are  experiential  Marketing  (X1), Emotional Branding (X2), Brand Trust (X3) as its independent variables; and Brand Loyalty (Y) as its dependent variable. To measure these variables, this study employed Semantic Dif- ferential Scale by using interval as its scale of measurement. 120 respondents of Honda mo- torcycle users were taken as sample of research from the population of Honda motorcycle users in Surabaya, with SEM (Structural Equation Modeling) employed as data analysis technique. On the one hand, the SEM analysis results revealed the positive and significant relationship of experiential marketing and brand trust on product loyalty. On the other hand, the analysis did not prove the significant nor positive influence of emotional branding to- wards loyalty.